2015
DOI: 10.1177/073953291503600107
|View full text |Cite
|
Sign up to set email alerts
|

Incivility Dominates Online Comments on Immigration

Abstract: An analysis of reader comments on the sites of three online newspapers in border states finds a much higher percentage of uncivil comments following stories about immigration than those following stories about the Tea Party.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 6 publications
2
28
0
5
Order By: Relevance
“…The study of impoliteness in the context of computer-mediated communication (CMC) has flourished in the recent decade encompassing various digital platforms of communication such as e-mail (Graham, 2005), discussion boards or forums (Nishimura, 2008;Upadhyay, 2010;Lorenzo-Dus & Blitvich, 2011), and social media such as Facebook, Instagram, Twitter, and YouTube (Pihlaja, 2011, Rowe, 2013Wang & Silva, 2018). Previous researchers have looked into impoliteness strategies used in various online communication platforms and found similar aspects of linguistic styles and patterns used by different groups of online users (Anderson, 2012;Santana, 2015). A similar finding was established by Oz, Zhen & Cheng (2018) who compared Twitter and Facebook to discover the equivalent level of impoliteness in both sites.…”
Section: Studies On Online Impolitenessmentioning
confidence: 99%
“…The study of impoliteness in the context of computer-mediated communication (CMC) has flourished in the recent decade encompassing various digital platforms of communication such as e-mail (Graham, 2005), discussion boards or forums (Nishimura, 2008;Upadhyay, 2010;Lorenzo-Dus & Blitvich, 2011), and social media such as Facebook, Instagram, Twitter, and YouTube (Pihlaja, 2011, Rowe, 2013Wang & Silva, 2018). Previous researchers have looked into impoliteness strategies used in various online communication platforms and found similar aspects of linguistic styles and patterns used by different groups of online users (Anderson, 2012;Santana, 2015). A similar finding was established by Oz, Zhen & Cheng (2018) who compared Twitter and Facebook to discover the equivalent level of impoliteness in both sites.…”
Section: Studies On Online Impolitenessmentioning
confidence: 99%
“…Løvlie, Ihlebaek and Larsson (2018) stated the experience of commenting is particularly meaningful for those whom oppose to a specific media outlet. Santana (2015) concluded that negative discourses in these spaces tend to increase towards immigration issues, based on a survey at sites of three online newspapers in Border States.…”
Section: Media Producers and Journalists' Perceptions On Interactivitymentioning
confidence: 99%
“…La materia migratoria es uno de los temas más polémicos en los comentarios de los usuarios. Así algunas investigaciones sobre comentarios a textos periodísticos vinculados al tema encontraron que las intervenciones negativas eran mayoría, que abundaban las de corte racista (Ferré y Simelio, 2016; y una marcada tendencia hacia un diálogo incivilizado tocante a la migración y los migrantes (Santana, 2015). Además, se ha destacado que la materia migratoria es una de las más complejas de moderar debido a la gran cantidad de mensajes Migración, racismo y xenofobia en internet: análisis del discurso de usuarios • Eduardo TorrE CanTalapiEdra contra los migrantes haitianos en prensa digital mexicana inadecuados que se producen (Ruiz et al, 2010;Diakopoulos y Naaman, 2011;Harris et al, 2014).…”
Section: Comentarios De Los Usuarios En Materia Migratoriaunclassified